Comparing of the efficacy of antacid and combination of antacid and H2RA on active nonvariceal upper gastrointestinal bleeding - Ali ERGİN,; Kadir AKSÖZ,; Günay ÖNDER,; Uğur GÖNENÇ,; Nafi YAZICIOĞLU,; Belkıs ÜNSAL,; Himmet KARACA,; Sadun KOŞAY, (Turkish Journal of Gastroenterology, 2020)
-